Detection of Multi-drugs Resistant Gram-negative bacilli Bacteria Producing Metallo Beta Lactamases in Intensive care unit of Sebha Medical Center, Sebha, Libya. - Aisha Almabrook Alrbee; Abdelkader A.Elzen; Allaaeddin A.El Salabi (Journal of Pure & Applied Sciences, 2022)
Antibiotic resistance of bacteria in health care settings has increased globally. Hospital infections caused by Multi drug resistant Gram-negative bacteria are serious problem, which results in very limited treatment options, consequently, leading to an increase in the mortality rates in hospitals worldwide. This study was conducted to detect the spread of multi drug resistant Gram-negative bacteria that producing Metallo β-Lactamase enzymes in the intensive care unit of Sebha Medical Center. Thirty six isolates of multi drug resistant Gram-negative bacteria were isolated from intensive care unit rooms. The most frequent isolates in the swabs taken from patients and medical staff in intensive care rooms included Rahnella aquatilis (31.3%), Enterobacter cloacae (31.3%), Pseudomonas aeruginosa (12.5%), Burkholderia cepacia (12.5%), Aeromonas hydrophila (6.3%) and Ochrobactrum anthropi (6.3%). Bacterial isolates from the ICU environment and hands of medical staff in the intensive care unit were Providenecia alcalifaciens (35%), Rahnella aquatilis (30%), Pantoea Spp (15%), Proteus mirabilis (10%),Enterobacter cloacae (5%), and Aeromonas salmonicida (5%). The most effective antibiotics against the Multi drug resistant Gram-negative bacteria isolated from the intensive care unit rooms are Gentamicin, Amikacin and Tobromycin proposing these antibiotics as potential treatment options for infections caused by MDR Gram-negative bacteria. The results also showed that the rate of MβL enzymes secretion by bacteria isolated from the ICU was (33%), as Pantoea Spp isolates were the most producers of MβL enzymes.